Domain Decomposition Methods with Nonmatching Grids for the Unilateral Problem (Journal of Computational Mathematics, 2002)
This paper is devoted to the construction of domain decomposition methods with nonmatching grids based on mixed finite element methods for the unilateral problem. The existence and uniqueness of solution are discussed and optimal error bounds are obtained. Furthermore, global superconvergence estimates are given.
Keywords: Domain decomposition; Variational inequality; Global superconvergence; Non-matching grids.